Implementation of home gardens with rural families of Medina Cundinamarca township to support the food security program (Revista Sistemas de Producción Agroecológicos, 2012)
The project objective was to implement the properties backyards twenty peasant families Medina Cundinamarca township to support the food security program in order to strengthen educational and productive activities aimed at providing a better quality of life. Also, they tried to develop an agroecological production that would allow the consumption of households. It also tried to promote food security in rural families to contribute to their well-being, also provided advice and technical assistance for proper development of the gardens. A total of 24 gardens were installed, as follows: Six schools in every village where the training took place, and the remaining one per family, which were developed in the homes of the people enrolled in the project. Along with these gardens, of the 100 families enrolled in the food security program but did not participate in the project, 68 were located in their homes and 32 did not participate in the process due to lack of land or negligence of some people. The results were that of cucumber seeds, beans, lettuce, onion, cilantro, beans, corn and paprika incorporated into the gardens, families collected food for their own consumption.
Keywords: home garden; food security; agroecology